Politik Hukum Amandemen UUD 1945 Dan Sistem Pemerintahan - Peri Pirmansyah (Fakultas Hukum Universitas Islam Indonesia, 2007)
Normatively the amendment of Indonesian Constitution 1945 implemented pure presidential system. However, the sytewm is not compatible with the multy parties system which is viasible based on the amendment. Thus, to maintain the presidential system, it needs further regulations in the form of Act concerns to more simple party system to support presidential system.